Geology And Mineralization Of The Santa Rosa Gold Deposits, Panama (db14143c-3c9a-4e78-82ee-0b3a79359f96) - Don C. White (Society for Mining, Metallurgy & Exploration, 1993)
Santa Rosa is a mid-Tertiary, volcanic-hosted, bulk-mineable, open-pitable, heap-leachable, gold-silver deposit. It is the product of hydrothermal mineralization along an arcuate segment of a caldera collapse ring fault in a probable maar volcanic setting. This segment was later broken by radial faults. Gold occurs principally as electrum finely disseminated through intermediate tuffs, and associated with pyrite, at Santa Rosa. The nearby Alto de la Mina deposit displays stockwork silica-pyrite-gold in a tectonically and hydrothermally shattered andesite flow. Miocene epithermal mineralization was accompanied by central silicification and pyritization and more distal argillization. An andesite flow cap rock at Santa Rosa played a pivotal role as an upward permeability barrier. Highest gold grades and most intense alteration occur closest to the ring faults and immediately beneath the andesite flow. Supergene alteration effects on the gold distribution are minimal.